Quantitative methods for evaluating the performance mechanism of management of financial flows - S. M. Khairova; B. G. Khairov (Вестник СибАДИ)
The article identifies factors rationalization of financial flows. Considered the content of the control mechanism of financial flows. The content of the financial and economic approach based on identifying what the maximum income can be obtained by alternative use of financial resources, which corresponds to the content of cash flow management mechanism. It was determined that the EVA theory, allows you to create, monitor, guide and evaluate decisions in the key value-adding in the optimization of financial flows.